Garcinia flavonoids for healthy aging : Anti-senescence mechanisms and cosmeceutical applications in skin care - Idris Adewale, Ahmed; Nor Hisam, Zamakshshari; Maryam Abimbola, Mikail; Ibrahim, Bello; Md. Sanower, Hossain (Elsevier B.V., 2024)
Cellular senescence, the irreversible arrest of cell division, is a hallmark of aging and a key contributor to agerelated disorders. Targeting senescent cells represents a promising therapeutic approach to combat these ailments. This review explores the potential of Garcinia species, a genus rich in flavonoids with established antioxidant and anti-inflammatory properties, as a source of natural anti-senescence agents. We investigate the intricate connections between aging, cellular senescence, and oxidative stress, highlighting the detrimental effects of free radicals on cellular health. Furthermore, we analyze the diverse array of flavonoids identified within Garcinia and their established cellular mechanisms. We critically evaluate the emerging evidence for the antisenescence potential of flavonoids in general and the limited research on Garcinia flavonoids in this context. By identifying existing knowledge gaps and paving the way for future research, this review underscores the exciting potential of Garcinia flavonoids as natural anti-senescence agents. These agents hold promise for not only promoting healthy aging but also for the development of cosmeceutical products that combat the visible signs of aging.